Remote hearing aid fitting: Tele-audiology in the context of Brazilian Public Policy - Silvio Pires Penteado; Sueli de Lima Ramos; Linamara Rizzo Battistella; Silvio Antonio Monteiro Marone; Ricardo Ferreira Bento (International Archives of Otorhinolaryngology, 2012)
Summary